Biophysical studies of the gingival epithelium - H S Grover; Himanshu Dadlani (Wolters Kluwer Medknow Publications, 2011)
Objectives: As the gingival epithelial cells undergo transition between the surface, crevicular and junctional areas, it is reported that their resting potential could also get altered due to change/variations in the membrane transport protein composition. Hence, the purpose of the present study is (i) to study the biophysical properties of the surface, the crevicular, and the junctional epithelial gingival cells and to assess their implications to the cell to cell and the cell to tooth attachment mechanisms; (ii) to study the effect of certain delipidifying agents such as Sodium Deoxycholate (DOC) and Sodium Dodecyl Sulfate (SDS) on the transmembrane electrical activity of the gingival epithelial cells; and, (iii) to study the histological changes due to these treatments and assess their bearings on the biophysical observations. Materials and Methods: The biophysical and histological investigations on the healthy human gingival epithelium were carried out on the fresh biopsy material obtained from a homogeneous group of willing donors between 11-15 years of age, who were advised for extraction of first premolar due to orthodontic reasons. The biophysical measurement involved recording of the transmembrane potentials using glass ultra-microelectrodes. For histologic studies, the hematoxylin and eosin (H&E) staining of the tissue sections was performed. Results: The mean values of the membrane potential in the three types of the gingival epithelium cells vary appreciably. While it was lowest in the junctional cells (2.83 ± 0.98 mV), it was highest in the surface epithelial cells (22.96 ± 5.19 mV). The crevicular cells showed a value greater than the junctional cells but lesser than the surface cells (9.3 ± 1.73 mV). Conclusion: The membrane transport protein density appears to decrease in the following order: surface > crevicular > junctional cells. The crosslinking force of calcium (Ca 2+ ) ions with their increased magnitude from the junctional epithelial cells to the cementum or enamel of the tooth appears to be the most convincing model of the epithelial attachment at the Dentoenamel (DE) junction.